Quantum cryptography and computing--theory and implementation - Horodecki, Ryszard; Kilin, S. I͡A. (Sergeĭ I͡Akovlevich); Kowalik, Janusz S. (NATO science for peace and security series. Information and communication security ;, 2010)
This volume contains papers presented at the NATO Advanced Research Workshop September 9-12, 2009, "Quantum Cryptography and Computing: Theory and Implementation", that was held in Sopot, Poland and organized by the National Quantum Information Centre of Gdansk. The papers are related to three broad subjects. The first is quantum cryptography, which includes technical and experimental issues and theory in a wide range of topics from the fundamental information-theoretical to commercial quantum cryptoraphy. The second subject is quantum computing, in particular, some quantum algorithms are analyzed and basic restrictions for quantum memory are presented. The last part is closely related to the physics of quantum information processing. It includes slid state devices for quantum information processing, quantum memories and superadditivity effects for quantum resources. The book is of interest and recommended to researchers and graduate students of experimental and theoretical quantum information. It unique feature is contributions by experts from both the West and the former Soviet Union.